Modern Iran : roots and results of revolution - Keddie, Nikki R. (Yale University Press, 2006)
This title brings the story of modern Iran to the 21st century, exploring the political, cultural, and social changes of the past quarter century. The author provides insightful commentary on the Iran-Iraq war, the Persian Gulf War, and the effects of 9/11 and Iran's strategic relationship with the US.